Reaction of diaryl-1,2-diones with triphenylphosphine and diethyl azodicarboxylate leading to N, N-dicarboethoxy monohydrazones via a novel rearrangement - Nair, Vijay; Biju, Akkattu T.; Abhilash, K. G.; Menon, Rajeev S.; Eringathodi, Suresh (Organic Letters, 2005)
A mechanistically novel reaction of diaryl-1,2-diones with diethyl azodicarboxylate and triphenylphosphine to afford N,N-dicarboethoxy monohydrazones is described. The reaction proceeds via a nitrogen to nitrogen migration of a carboethoxy group.

Recent advances in employing homoenolates generated by N-heterocyclic carbene (NHC) catalysis in carbon-carbon bond-forming reactions - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Chemical Society Reviews, 2015)
The use of NHCs for generating homoenolate species has gained widespread popularity in recent years. A number of highly stereoselective processes of NHC-homoenolates have emerged. Homoenolate reactions have also been employed as key steps in the total synthesis of a number of natural products. The use of compatible co-catalysts, improved NHC-catalyst design and the use of novel precursors for homoenolate generation are among the major developments in this area that were disclosed recently. This tutorial review organises and presents the advancements in this rapidly growing area of catalysis and in the process updates a previous account published in 2011 in this journal.

Recent advances in N-heterocyclic carbene (NHC)-catalysed benzoin reactions - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Beilstein Journal of Organic Chemistry, 2016)
N-Heterocyclic carbenes (NHCs) have emerged as a powerful class of organocatalysts that mediate a variety of organic transformations. The Benzoin reaction constitutes one of the earliest known carbon-carbon bond-forming reactions catalysed by NHCs. The rapid growth of NHC catalysis in general has resulted in the development of a variety of benzoin and benzoin-type reactions. An overview of such NHC-catalysed benzoin reactions is presented.
Keywords: acyloin reaction; benzoin reaction; N-heterocyclic carbenes; organocatalysis; umpolung

Recent advances in N-heterocyclic carbene (NHC)-catalysed benzoin reactions (vol 12, pg 444, 2016) - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Beilstein Journal of Organic Chemistry, 2016)
Keywords: acyloin reaction; benzoin reaction; N-heterocyclic carbenes; organocatalysis; umpolung